Distribution of extended-spectrum β-lactamase types in a Brazilian tertiary hospital - Keite da Silva Nogueira (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: Epidemiological data on the prevalence of extended-spectrum β-lactamases (ESBLs) are scarce in Brazil despite the fact that these data are essential for empirical treatment and control measures. The objective of this study was to evaluate the prevalence of different ESBLs by type and distribution in a tertiary hospital in southern Brazil. METHODS: We evaluated 1,827 enterobacterial isolates between August 2003 and March 2008 isolated from patients at a tertiary hospital. Samples were identified using a Vitek automated system and were confirmed by biochemical testing. The identified ESBL strains were characterized by phenotypic methods, polymerase chain reaction (PCR), and sequencing. Genetic similarities were evaluated by pulsed-field gel electrophoresis. RESULTS: It was 390 (21.3%) ESBL-producing strains, which expressed the ESBLs CTX-M (292), SHV (84), CTX and SHV (10), TEM (2), and PER (2). CONCLUSIONS: The prevalence of ESBL-expressing strains was high, especially in Klebsiella pneumoniae and Enterobacter spp. CTX-M was the predominant type of ESBL observed, and its genetic variability indicates a polyclonal distribution.